Penerapan Giving Question And Getting Answer Untuk Meningkatkan Keaktifan Belajar Matematika Kelas XI SMK Muhammadiyah Kartasura - Yoshivan, Retiana, Drs. Ariyanto, M.Pd (2017)
ABSTRACT This research was conducted in order to improve the activity and interest of students in learning mathematics through the implementation of cooperative learning strategies type of Giving Question and Getting Answer. This research used the qualitative approach. The qualitative method is the method used to get the data containing the meaning, where researchers into data collection instruments, using the technique of triangulation. Design research is the research action class (PTK). The subject receiving the action was the XI grade students of OA SMK Muhammadiyah Kartasura, 28 students. Giving Question and Getting Answer method is a learning method that will train the students to reconstruct their own knowledge whereas the teacher play role as the facilitator. Based on the results of the research, obtained an increase in the percentage of activity and interest in learning mathematics. It was proven by the percentage of students who actively taking note, from 16 students (57,10%) increse to 26 students (92,80%), students who actively doing homework, from 13 students (46,40%) increase to 26 students (92,80) %), And students who actively delivering and answering question, from 5 students (17.50%) increase to 16 students (57.10%). Based on the result, it is concluded that the implementation of Giving Question and Getting Answer strategy can increase the activity of students in learning mathematics. Keywords :giving question and getting answer, learning activity, mathematics study.